Impact of a Time-Related Benchmark on the Adenoma Detection Rate in Surveillance Colonoscopy: A STROBE Statement-Oriented Cross-Sectional Cohort Study - Ban, Tesshin; Kubota, Yoshimasa; Yano, Tomonori; Mieno, Makiko Naka; Takahama, Takuya; Sasoh, Shun; Tanida, Satoshi; Ando, Tomoaki; Nakamura, Makoto; Joh, Takashi (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Colorectal adenomas are precursor lesions of globally increasing colorectal cancer. Hence, a high adenoma detection rate in colonoscopy is pivotal. We investigated the clinical impact of stratified colonoscopy observation time combined with observation time/intubation time ratio on the detection of colorectal adenomas. Materials and Methods: We conducted a single-center retrospective study including 369 consecutive patients who underwent colonoscopy following fecal immunochemical tests between May 2021 and April 2022. The primary outcome measure was the impact of the stratified observation time and observation time/ intubation time ratio (category 1: <6.0 minutes and <1.0, category 2: <6.0 minutes and ≥1.0, category 3: ≥6.0 minutes and <1.0, and category 4: ≥6.0 minutes and ≥1.0) on adenoma detection rate. Results: Cecum intubation was obtained in 367 patients (99.5%). Adenomas were detected in 226 patients (61.2%). From the univariate analysis, age ≥53 years, habitual alcohol intake, colonoscopy attachment (+), and observation time with observation time/intubation time ratio categories 3 and 4 were determined as significant factors for adenoma detection rate. From the logistic regression analysis, age ≥ 53 years (odds ratio: 4.86, 95% CI: 2.25-10.52), habitual alcohol intake (odds ratio: 2.26, 95% CI: 1.33-3.82), category 3 (odds ratio: 3.66, 95% CI: 1.81-7.45), and category 4 (odds ratio: 5.60, 95% CI: 2.92-10.73) were significant factors for adenoma detection rate. Conclusion: We propose the observation time with observation time/intubation time ratio combined benchmark (with categories’ thresholds based on observation time >6 minutes and scope withdrawal time exceeding intubation time [observation time/intubation time ratio > 1]) as a novel colonoscopy quality indicator. These findings represent an important educational message for endoscopists.